Reimagining Gender Identities in Gone Girl: A Jungian Archetypal Analysis of the Collective Unconsciousness - Fahim, Sana; Ayub, Samina (Pakistan Languages and Humanities Review, 2025)
This study aims to explore how the writer challenges as well as critiques gender stereotypes in the novel Gone Girl written by Gillian Flynn. Departing from the stereotypical characterization, the novel present characters that constantly sway between the traditional masculine and feminine traits. A qualitative research design was employed to map the characters’ actions from a psychological perspective. The findings of the study suggest that the traditional male and female stereotypes that have been glorified in the American society for a long time do not have any scientific basis. Instead they are just over- generalizations of ascribed traits associated with men and women within the institution of marriage. The future researches may extend the Jungian theoretical framework to non- Western narratives in order to reshape the socio-cultural perceptions of gender and identity. Furthermore, the comparative analysis of male and female archetypes within different contemporary novels can uncover new dimensions of gender representations